2011
DOI: 10.4081/vsd.2011.e8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive immunization by anti-gingipain IgY on periodontal health of dogs

Abstract: Anti-gingipain IgY (IgY-GP), known as hyperimmune γ-livetin from egg yolk, inhibits the enzyme activity, growth and adherence of Porphyromonas gingivalis to gingival epithelial cells. Our objective was to evaluate the efficacy of IgY-GP on periodontal health of dogs. IgY-GP was prepared from the egg yolk of hens immunized with the gingipain from Porphyromonas gingivalis ATCC 33277. Two in vivo trial models were conducted on 15 adult dogs with periodontitis by giving IgY-GP-supplemented dog feed for 8 weeks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Also, it is possible that the IgY may not penetrate deep into periodontal pockets. 20 Porphyromonas gingivalis is an anaerobic gram-negative bacteria and the periodontal pocket is the ideal environment for its proliferation. 32 This can be a possible explanation for the lack of reduction in the relative abundance of P gingivalis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, it is possible that the IgY may not penetrate deep into periodontal pockets. 20 Porphyromonas gingivalis is an anaerobic gram-negative bacteria and the periodontal pocket is the ideal environment for its proliferation. 32 This can be a possible explanation for the lack of reduction in the relative abundance of P gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors reported that dividing the amount of IgY-GP into 2 daily meals, the effect is lower than in 1 daily meal. 20 Cats received an average of 46.5 mg of IgY-GP/kg BW, but the food was available during consecutive 16 hours and they presented high food intake during the first 2 hours (approximately 23.5 mg of IgY-GP/kg BW), with small consumption during the remaining period (approximately 3.3 mg of IgY-GP/ kg BW each 2 hours). This might explain the lack of reduction in the majority of oral health parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plaque, a microbial biofilm, is recognized as a main etiological agent for periodontal disease [138]. The oral immunotherapy by using anti-gingipain IgY has been reported to improve significantly periodontal health of dogs when applied directly into some periodontal pockets in the form of ointment [139]. Anti-gingipain IgY was obtained from the egg yolk of hens immunized with gingipain, a protease from Phorphyromonas gingivalis, which Sharifiqur et al [139] considered to be a major periodontal pathogen, based on data obtained with humans, mice and rats.…”
Section: Adaptive Immunity / Passive Immunotherapymentioning
confidence: 99%